PAD patients present with poorer lipid target attainment than polyvascular patients – a call for intensified treatment. (25th November 2020) - Dopheide, J.F; Adam, L; Khorrami Borozadi, M; Kaspar, M; Baumgartner, I; Drexel, H
Abstract: Background: Due to the very high risk of future cardiovascular events, strict lipid lowering therapy is recommended in patients with peripheral artery disease (PAD). However, data on target level attainment and statin adherence is scarce, especially when the atherosclerotic burden is extended to other vascular beds, i.e. coronary artery disease (CAD) and/ or cerebrovascular disease (CeVD). Purpose: We hypothesized that patients with PAD alone have poorer lipid target attainment than polyvascular patients (+ CAD and/ or CeVD) and that an intensified statin therapy improves attainment of lipid targets and thus survival of patients with PAD only. Methods: Single center longitudinal observational study with 1380 symptomatic PAD patients over a mean follow-up period of 60±32 months. We related statin adherence and LDL-C target attainment to all-cause mortality. Results: Initially, 58% of the PAD only patients were on statins in contrast to PAD patients with one (+1V (79%)) or two (+2V (80%)) further vascular regions. At follow up we observed an increase to 87% statin use (p<0.0001) in PAD only patients. Statin use in +1V and +2V patients increased as well (+1V: 92%; +2V: 87%). Lipid target attainment in PAD only (<55 mg/dl) was observed in only 10%, but increased to 19%. Statin dosage in PAD only patients, normalized to simvastatin 40 mg, increased from 46 to 52 mg/ day (p<0.01), and was paralleled by a mean decrease of LDL-C from 103 to 84 mg/ dL (p<0.0001). PAD only patients had a significant lower mortality rate (13%) than +1V (22%) or +2V patients (35%) (p<0.0001). Survival of PAD only patients significantly improved when having newly received a statin (11%), similar to those continuously on statins (10%). Moreover, patients on a high intensity statin medication had a low mortality of 10%. Those who terminated statin medication or never received a statin had a higher mortality (26%; p<0.01). Conclusion: Patients with a PAD only have a lower mortality than PAD patients where progression to one or two vascular beds occurred. Our data suggest that for PAD only patients an intensified statin therapy is then associated with reduced mortality. A strategy of intensive and sustained statin therapy as early as possible is recommended. Funding Acknowledgement: Type of funding source: None